The life marker chip : potential use of aptamers against small molecules and consideration of instrument planetary protection - Rato, Carla Cristina Pereira Salgueiro Catarino (Cranfield University, 2013)
The Life Marker Chip (LMC) instrument was developed with the aim to detect evidence of life on Mars. The detection was based on an inhibition immunoassay. In this work aptamers were evaluated as potential alternative to antibodies for the LMC. Aptamers were synthetic oligonucleotides able to bind specifically with high affinity to a wide range of target molecules, and have been also integrated as bioreceptors in several detection instruments. The generation of new aptamers against two small molecules using the FluMag-SELEX method was tested and was verified the adaptability of pre-existing aptamers against small targets to the LMC assay type. Based on the fact that the LMC was going to be integrated into the space programme ExoMars, it was also implemented into a small scale experiment the Planetary Protection and Contamination Control requirements found on a life-search mission. In addition to that aptamers compatibility with a sterilisation procedure used in life-search missions was also tested. Furthermore because of the nature of the small molecules studied, multiple analytical chemistry techniques were assessed to verify covalent chemistry surface immobilisation. Within the project timeline it was not possible to achieve a full aptamer generation process but it was possible to understand the methodology behind the procedure and give input for future work. It was found that the direct implementation of existing aptamers against small molecules into the LMC assay was not successful. It was also seen that in the case of aptamer integration onto the LMC some assay changes would probably have to be made. This information was very useful to understand if aptamers could be an alternative to antibodies and be implemented directly into the LMC. It was found that aptamers survived the preliminary sterilisation method applied, which might open the possibility of making aptamers convenient space bioreceptors, reducing time and costs of instrument Planetary Protection implementation. In conclusion aptamers were not straightforward alternatives to antibodies for the LMC because aptamers interacted differently with their targets in comparison to antibodies, particularly with small molecules. Also the biochemical simplicity of the small molecule targets introduced difficulties in aptamers generation that more complex targets would have not. Although aptamers shown incompatibility with the LMC assay format against small targets, they presented resilience to a sterilisation procedure implemented on space missions which could lead to the development of more robust bioreceptors for space missions. This information was helpful in understanding which assay formats were better for detection of small molecules using aptamers and that might contribute for future assay choices applied in detection instruments. It was also possible to make recommendations for the LMC regarding design and validation methods used in life-search missions based on the lessons learn from the developed of a small scale experiment. The developed work was presented at conferences and mentioned in an article journal, and in that way contributed to the knowledge of the space community in general.
Keywords: ExoMars; Mars; life-search; bioreceptor; FluMag-SELEX; ELAA; surface immobilisation; PP&CC; CASS·E